Boundary condition modifications of the Suzen-Huang plasma actuator model - Ibrahim, Imran H. (2014)
The accuracy of the Suzen-Huang (S-H) model is improved by altering the boundary condition of the dielectric surface above the lower electrode. For the equation governing the electric field, we introduce a ‘dielectric shielding’ condition at the same region, which results in a spread of the electric field strength along the dielectric surface. For the equation governing the surface charge density, we introduce boundary conditions that modify the behavior of the charge density variable in the S-H model. The conditions represent a fitting procedure by adding the features of propagation and dissipation in a one-dimensional Fokker-Plank equation. The equation is initiated by a normal distribution function centered at the leading edge of the lower electrode. These modifications improved model results by about 50% when comparing the maximum induced velocity value with experimental results. Furthermore, charge density growth is propagating in a similar manner to that obtained by charge transport models.